JENIS TUMBUHAN PEWARNA ALAM YANG DIMANFAATKAN OLEH MASYARAKAT PENENUN DESA BATU LINTANG KECAMATAN EMBALOH HULU KABUPATEN KAPUAS HULU - Kartini, Dayang Eva; Sisillia, Lolyta (Universitas Tanjungpura, 2017)
Forest has many resources which used by the community with their local wisdom. The weaver community from Dayak Iban tribes in Batu Lintang village, Embaloh Hulu district, Kapuas Hulu regency, West Kalimantan province used traditional natural dyes for their product. The natural dyes achieved from the forest near their village. This study aimed to exploration the types of natural dyes uses by the weaver community in Batu Lintang village, Embaloh Hulu district, Kapuas Hulu regency, West Kalimantan province. Methodology of research used in-depth interview to the weaver and exploration the plants in the forest. Result of the research showed that seven species of natural dye used daily in the village. The name of the plants were Tarenna fragrans (Rubiaceae), Psychotria malayan (Rubiaceae), Morinda citrifolia (Rubiaceae), Peristrophe bivalvis (Acanthaceae), Clerodendrum laevifolium (Lamiaceae), Senna siamea (Fabaceae), and Eusideroxylon zwageri (Lauraceae). They used the leaf, root and stem of the plant. The color from Tarenna fragrans and Morinda citrifolia was brown, Psychotria malayan was red brown, Peristrophe bivalvis and Eusideroxylon zwageri was red, Clerodendrum laevifolium and Senna siamea was green and black. The community of Batu Lintang village still maintained the tree in the forest. These traditional natural dyes need preservations and technology to get the better result for their products.Keywords: Batu Lintang village, Dayak Iban, Kapuas Hulu, natural dyes, woven fabrics